Fitoquímica de Raputia praetermissa (Rutaceae) e busca por candidatos a herbicidas inibidores da fotossíntese a partir de produtos naturais - Veiga, Thiago André Moura (2008)
The species R. praetermissa is native from Amazonia. Plant recently classified, it does not give biological and/or chemical in the literature. This fact has led to this study, which can lead to the correct chemosystematic positioning of the genus within the family Rutaceae. From the phytochemical study of the roots of R. praetermissa concluded in 2005, mainly were found alkaloids derived from tryptophan and limonoids. The second step was the phytochemical study of some fractions of the dichloromethane extract of the roots and the extracts of the stem and leaves of the species. Alkaloids have been isolated and identified (indole, furoquinolines and quinolones), triterpenes (cycloartanes and friedelanes), steroids and a derivative of cinnamic acid. Among the substances found can highlight four substances not reported in the literature: two alkaloids, a diterpene and the derivative of cinnamic acid. A collection of 120 natural products isolated by the group of Natural Products/UFSCar was subjected to a series of enzymatic reactions that explained the mechanism of action of the substances considered active against photosynthesis in vitro in chloroplasts isolated from the leaves of spinach. It was possible to clarify the mechanism of action of 30 substances, which allowed so far, the publication of articles in indexed international journals and conferences (nationals and internationals). The prospects are quite interesting, especially as regards the implementation of this new line of research, not only in the Department of Chemistry (UFSCar), but also in Brazil, so that later are found models for new herbicides inhibitors of photosynthesis.